Unheard voice of a talented woman subject to double discrimination: narratives of womanhood with physical constraints and her unique learning experiences - Khaskhely, Mahvish Kanwal; Shamsi, Aamir Firoz; Channar, Sheeba; Naqvi, Iffat Batool (International Journal of Psychosocial Rehabilitation, 2020)
This narrative account discuss the struggles and experiences of a young woman with multiple lifelong diseases (Retinitis Pigmentosa and Rheumatoid Arthritis) in a society which lacks proper awareness regarding such diseases. Traditional societies seek conformity and in the process increase burden of expectations on already fragile individuals especially women with debilities. The methodology undertaken to retell the experiences of the participant is narrative inquiry in which thematic analysis is conducted to identify various emerging themes which provide insights to her struggles deepened by the double discrimination arising from her gender and disability. Such concerns are discussed via the themes of sympathy and empathy, and unrealistic expectations among others. By providing the narrative of differently able woman in conservative society, this study attempts to listen to her previously unheard voice to increase general awareness and understanding towards the lives and experiences of women with physical hindrances, gearing reader’s thought process towards their support on multiple levels. 2011 International Transaction Journal of Engineering, Management, & Applied Sciences & Technologies. Some Rights Reserved.